GPI-microdomains: a role in signalling via immunoreceptors - Horejsí, V; Drbal, K; Cebecauer, M; Cerný, J; Brdicka, T; Angelisová, P; Stockinger, H (Immunology today, 1999)
Glycosylphosphatidylinositol (GPI)-anchored proteins and glycosphingolipids are assembled on the leukocyte surface within membrane microdomains, which also accommodate a set of cytoplasmic signalling molecules (Src family kinases, G-proteins, linker proteins). Recent results suggest that these membrane specializations mediate not only signal transduction via GPI-proteins and glycolipids but also play important roles in initiation of signalling via immunoreceptors.
Keywords: buněčná membrána; receptory imunologické; signální transdukce; Glycosylphosphatidylinositols; membránové proteiny; Membrane Proteins; Models, Biological; glykosylfosfatidylinositoly; Receptors, Immunologic; Signal Transduction; Animals; Cell Membrane; Humans; lidé; zvířata; Leukocytes; leukocyty; biologické modely